Nikolay Ivanovich Khvisyuk - KhMAPE, Staff (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
January 19, 2019 was the 85th anniversary of the birth of the famous scientist, organizer of health care and higher education, a brilliant orthopedist-traumatologist, Honored Worker of Science and Technology of Ukraine, Doctor of Medical Sciences, Professor at the Department of Medical Faculty of Kharkiv National University. V.N. Karazin, Honorary Rector of the Kharkiv Medical Academy of Postgraduate Education, Honorary Citizen of the Kharkiv Region Nikolay Ivanovich Khvisyuk.